(untitled) (Research, Society and Development, 2024)
The number of people who adhere to vegetarianism or veganism has grown and impacted the gastronomic market, which has had to adapt to meet this demand. Given this scenario, the present study aimed to investigate the offer of options for this public in the “Comida di Buteco” competition in Belo Horizonte, Minas Gerais, known nationally as the world capital of bars. This is a descriptive and exploratory research carried out between April and September 2023. Data collection about the preparations offered in the last 10 editions, covering the period between 2013 and 2023, was carried out on the official website of the competition, in addition to specialized websites in gastronomy, newspaper and magazine reports. The information in the preparation description made it possible to classify them as: vegetarian, vegan or omnivorous. Data analysis showed that only in 2019 was there a vegan and a vegetarian preparation on offer, representing 1.92% of the 52 preparations served this year. Thus, the results demonstrated a limited supply of vegetarian and vegan options in the preparations competing in “Comida di Buteco” in the last 10 editions, suggesting a dissonance of the preparations offered in the competition with the growing vegan and vegetarian market.